Identification and Functional Analysis of Two New Mutant BnFAD2 Alleles That Confer Elevated Oleic Acid Content in Rapeseed - Long, Weihua; Hu, Maolong; Gao, Jianqin; Chen, Song; Zhang, Jiefu; Cheng, Li; Pu, Huiming (Frontiers in Genetics, 2018)
Rapeseed (Brassica napus L.) is a vital oil crop worldwide. High oleic acid content is a desirable quality trait for rapeseed oil, which makes it more beneficial to human health. However, many germplasm resources with high oleic acid content in rapeseed have not been evaluated with regard to their genotypes, making it difficult to select the best strains with this trait for the breeding of high oleic acid rapeseed variety. This work was to explore the gene-regulation mechanism of this trait using a new super-high oleic acid content (∼85%) line N1379T as genetic material. In this study, the sequences of four homologous fatty acid desaturase (BnFAD2) genes were compared between super-high (∼85%, N1379T) and normal (∼63%) oleic acid content lines. Results showed that there were two single-nucleotide polymorphisms (SNPs) in BnFAD2-1 and BnFAD2-2, respectively, which led to the amino acid changes (E106K and G303E) in the corresponding proteins. Functional analysis of both genes in yeast confirmed that these SNPs were loss-of-function mutations, thus limiting the conversion of oleic acid to linoleic acid and resulting in the considerable accumulation of oleic acid. Moreover, two specific cleaved amplified polymorphic sequences (CAPS) markers for the two SNPs were developed to identify genotypes of each line in the F2 and BC1 populations. Furthermore, these two mutant loci of BnFAD2-1 and BnFAD2-2 genes were positively associated with elevated oleic acid levels and had a similar effect with regard to the increase of oleic acid content. Taken together, these two novel SNPs in two different BnFAD2 genes jointly regulated the high oleic acid trait in this special germplasm. The study provided insight into the genetic regulation involved in oleic acid accumulation and highlighted the use of new alleles of BnFAD2-1 and BnFAD2-2 in breeding high oleic acid rapeseed varieties.